please give a solution
Attachments:
![](https://hi-static.z-dn.net/files/d6c/2916b0195c87fc69b4b630ec1def9d6a.jpg)
Answers
Answered by
0
I hope this will help uu plzz mark me brainlist plzzz if it will help uuu byy
Attachments:
![](https://hi-static.z-dn.net/files/d9e/886985a38ae03efbec25d5b94264addc.jpg)
Answered by
0
(1 + Cot A +Tan A ) ( SinA -CosA )
= SinA +CosA +Sin2A/CosA -CosA -Cos2AsinA -Sin A
=Sin2A/ CosA -Cos2A/SinA
= SecA/Cosec2A -Cosec/Sec2A
sinA(TanA) - CotA CosA
= Sin2A / cosA - Cos2A SinA
Sec2A/cosec2A - CosecA/Sec2A
LHS = CENTRE = RHS
hence proved
Similar questions
Social Sciences,
8 months ago
Chemistry,
8 months ago
Social Sciences,
8 months ago
Math,
1 year ago
Math,
1 year ago
Hindi,
1 year ago